Developing a profile website for mosque Qori and Imam as a medium for Da'wah - Adzanil Rachmadhi Putra; Rosyid Abdilah; Riza Akhsani Setyo Prayoga; Machfud Ichsan Khoirudin; Muhammad Taufikurrahaman; Shanaya Lubna Dio (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Information technology is getting faster and more advanced. Many activities utilize information technology in helping a job. Currently, information media is not only through print media but there are already media that utilize information technology to be able to reach the wider community. The emergence of websites has a positive impact on getting information widely and can be accessed anytime and anywhere. This provides the best solution for community service partners, namely Al-Barra Studio located in Malang City. Al-Barra Studio is engaged in video content, namely making video recordings for mosque Qori and Imam later people who are interested in using the services of mosque Qori or Imam can contact Al-Barra Studio. The development of this website uses parallel development with the help of using the concept of Custom Management System in the form of WordPress. It is hoped that the presence of this website can help in promotional media from Al-Barra Studio so that it can be known by the public at large and as a media for da'wah through information technology facilities.